Teater Mamanda dan Pendefinisian Kembali Identitas Banjar - Ninuk Kleden-Probonegoro (Antropologi Indonesia, 2002)
This article examines notions of identity in the context of Mamanda, a traditional theatre in Banjar, South Kalimantan. The author Mamanda as a cultural symbol and describes the formulation of its identity using a semiotic approach whereby identity is conceived as a part of a binary composition fluctuating between the opposing notions of 'us' and 'other'. This is illustrated in the oppositions between the theatre's community and the state, individuals and the state, and the contradictory oppositions between the community members within Mamanda itself. This article demonstrates that identity is continually reformulated and is linked to political interests such as regional autonomy.